ANALISIS PENJADWALAN SISTEM PERAWATAN PADA MESIN PADA CV RING TECH ENGINEERING - Tarihoran, Yulian Putri; Anggia Arista (LPPM Universitas Putera Batam, 2024)
CV Ring Tech Engineering is a type of business in the field of fabrication that processes machine jigs and fixtures and manufacturing equipment consisting of milling machines, grinding machines and lathes. The problem that occurs at CV Ring Tech Engineering is that there is damage to the lathe, thus hampering the pace of the production process. Some of the damage that occurs on the lathe is: belting is often loose, spindle vibration is unstable, cutting edges are often damaged or worn and the sled is difficult to shift. The purpose of this research is to determine the form of maintenance system scheduling on lathe machines at Cv Ring Tech Engineering The method used in this research is the RCM (Realiability Centered Maintenance) method. The results obtained The maintenance action on machine 01 was carried out a maintenance interval of 144.4 hours or 20 days, on machine 02 a maintenance interval of 182 hours or 7 days and on machine 03 a maintenance interval of 97.32 hours or 4 days.